Effectiveness of vaccines in preventing hospitalization due to COVID-19: A multicenter hospital-based case-control study, Germany, June 2021 to January 2022. Issue 2 (9th January 2023) - Stoliaroff-Pepin, Anna; Peine, Caroline; Herath, Tim; Lachmann, Johannes; Perriat, Delphine; Dörre, Achim; Nitsche, Andreas; Michel, Janine; Grossegesse, Marica; Hofmann, Natalie; Rinner, Thomas; Kohl, Claudia; et al.
Highlights: This study assesses detailed first-hand data and therefore provides a very high data quality. Detailed interviews, abstraction of medical records and laboratory analyses were combined to obtain comprehensive data sets. More than half of the cases (58 %) were not vaccinated at all, compared to 11 % of the controls. The vaccine effictiveness to prevent severe disease in the Delta wave was 89 % overall for two doses and 98 % for three doses. Abstract: We included 852 patients in a prospectively recruiting multicenter matched case-control study in Germany to assess vaccine effectiveness (VE) in preventing COVID-19-associated hospitalization during the Delta-variant dominance. The two-dose VE was 89 % (95 % CI 84–93 %) overall, 79 % in patients with more than two comorbidities and 77 % in adults aged 60–75 years. A third dose increased the VE to more than 93 % in all patient-subgroups.